Diagnosis of Spontaneous Bacterial Peritonitis and an In Situ Hybridization Approach to Detect an "Unidentified" Pathogen. (14th July 2014) - Enomoto, Hirayuki; Inoue, Shin-ichi; Matsuhisa, Akio; Nishiguchi, Shuhei
Abstract : Spontaneous bacterial peritonitis (SBP) is a frequent and severe complication in cirrhotic patients with ascites. Although identifying the pathogen(s) plays a major role in the management of infectious diseases, ascitic fluid cultures often show negative results in patients with clinical signs and symptoms of SBP, and ascitic fluid cell analyses are the gold standard method for diagnosing SBP. SBP is generally diagnosed based on an increased number of polymorphonuclear neutrophils in the ascitic fluid (> 250/mm 3 ), and the identification of the causal pathogen may not be given consideration. We newly developed an in situ hybridization (ISH) method to provide early and direct evidence of bacterial infection in ascites in patients with SBP. This paper will review the diagnosis of SBP, including our novel approach with ISH method to detect bacterial DNA in SBP ascitic fluid.